Consider Δ A B C having I as its incenter and I 1 , I 2 , I 3 as its excenters opposite to vertices A , B , C respectively.If Δ A B C has a unit circumradius , find the value of :
c y c { 1 , 2 , 3 } ∑ ( I I 1 2 + I 2 I 3 2 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Great observation of the change of perspective of the triangle. This is further motivated since the expression only involves I , I 1 , I 2 , I 3 .
It's nine point circle not nice point circle!!
As per standard trigonometric results we know the following things:
I I 1 = 4 R sin 2 A I I 2 = 4 R sin 2 B I I 1 = 4 R sin 2 C I 1 I 2 = 4 R cos 2 C I 2 I 3 = 4 R cos 2 A I 1 I 3 = 4 R cos 2 B I I 1 2 + I 2 I 3 2 = 1 6 R 2 sin 2 2 A + 1 6 R 2 cos 2 2 A = 1 6 R 2 ( sin 2 2 A + cos 2 2 A ) = 1 6 I I 2 2 + I 1 I 3 2 = 1 6 R 2 sin 2 2 B + 1 6 R 2 cos 2 2 B = 1 6 R 2 ( sin 2 2 B + cos 2 2 B ) = 1 6 I I 3 2 + I 1 I 2 2 = 1 6 R 2 sin 2 2 C + 1 6 R 2 cos 2 2 C = 1 6 R 2 ( sin 2 2 C + cos 2 2 C ) = 1 6
So the required sum = 1 6 + 1 6 + 1 6 = 4 8
Instead of saying Trigonometry, say "Using properties of Ex △ l e and Pedal △ l e , we get ⋯ "
And also say that I is the orthocentre of the E x △ l e I 1 I 2 I 3
Problem Loading...
Note Loading...
Set Loading...
Here is a solution without the use of Trignometry. It is well known that I is the orthocenter of I 1 I 2 I 3 , and ⊙ A B C is essentially the nice point circle of I 1 I 2 I 3 . Therefore we can reword the problem the following way: Given a triangle A B C with orthocenter H and circumradius 2 , find ∑ c y c A H 2 + B C 2 . (Note that half of the circumradius is the radius of the nine point circle.
We will show that A H 2 + B C 2 is actually constant, given the circumradius is fixed. To see this, let O denote the circumcenter of A B C , M is the midpoint of B C . It should be well known that 2 O M = A H , therefore A H 2 + B C 2 = 4 O M 2 + 4 M C 2 = 4 O C 2 = 4 ( 2 ) 2 = 1 6 . Hence our answer is 1 6 ∗ 3 = 4 8 .